Therapeutic potentials of hypoxic- and baicalein-enriched fraction-preconditioned human neural stem cells for in vitro ischemic stroke model - Nee, Kang In (2018)
Ischemic stroke is the third leading cause of death in Malaysia, closely after heart disease and cancer. Standard treatments for stroke are not totally efficient to repair and regenerate the damaged brain tissue and there are possibilities for the recurrence. Replacement by endogenous adult neural stem cells (NSCs) during ischemic stroke was insufficient to repair injury site due to low neuronal turnover that could integrate into functional neuron network. Therefore, it is imperative to develop alternative therapeutic strategies to improve stroke recovery. Recently, human NSC grafting has emerged as encouraging approach for treating stroke. Nonetheless, the therapeutic potential of NSC-based treatment is limited, mainly due to a large number of implanted cells died after grafting into the injury site. To circumvent this problem, this study aimed to enhance therapeutic potentials of human NSCs prior to transplantation through hypoxic and baicalein-enriched fraction (F5) preconditioning. Hypoxic preconditioning under 2% O2 for 24 h enhanced NSC self-renewal, survival and multipotency. 60S ribosomal protein large P1 (RPLP1) and ribosomal protein L13A (RPL13A) were the most reliable reference genes for qPCR normalization of normoxic- and hypoxic-preconditioned NSCs. Hypoxic preconditioning induced innate neuroprotective signaling through transcriptional activation of hypoxia-inducible factor-1 alpha (HIF-1α), vascular endothelial growth factor A (VEGFA), angiopoietin 1 (ANGPT1), neurogenic locus notch homolog protein 1 (Notch 1), nuclear factor erythroid 2-related factor 2 (Nrf2) and sodium dismutase 1 (SOD1). Based on the HIF-1α stabilization potential of baicalein at ambient conditions, F5 was postulated to trigger effects mimic hypoxic preconditioning under normoxia. Interestingly, preconditioning with 1.56 μg/mL of F5 for 24 h increased NSC proliferation, viability and lineage specific differentiation. Hypoxanthine phosphoribosyl transferase 1 (HPRT1) and RPL13A were the most stably expressed reference genes for qPCR normalization of control (0.1% DMSO) and F5-preconditioned NSCs. Moreover, F5 preconditioning stimulated hypoxiamimetic signaling intrinsically via HIF-1α, VEGFA, ANGPT1, Notch 1, Nrf2 and SOD1 upregulation. Both hypoxic- and F5-preconditioned NSCs were applied to in vitro ischemic stroke (IVIS) model on wound-healing based culture slide for 72 h of live imaging. F5-preconditioned NSCs accelerated migration and homing towards IVIS model over an experimental period of 72 h compared to hypoxicpreconditioned NSCs. The neuroprotective factors induced by hypoxic preconditioning are postulated to degrade rapidly when exposed to oxygen. Contrarily, F5-preconditioned NSCs attained intrinsic neuroprotective mechanisms without compromising their stability under normoxia. In conclusion, both the hypoxic and F5 preconditioning had successfully enhanced therapeutic potentials of NSCs for ischemic stroke. F5-preconditioned NSCs with enhanced therapeutic efficacy was more likely to be applicable in clinical setting and thus could be a promising therapeutic tool for ischemic stroke in the future.